Maternal and neonatal outcomes following antenatal corticosteroids in pregnancies complicated by diabetes: a scoping reviewAJOG Global Reports at a Glance - Klea Atallah, BBiomed(Hons); Serena Moon, MD; I-Lynn Lee, MBBS, BMedSc, FRACP, PhD; Rosalynn Pszczola, MBChB, BMedSci(Hons), FRACP; Joanne M. Said, MBBS, PhD, CMFM (AJOG Global Reports)
Objective: To examine the current literature surrounding the administration of antenatal corticosteroids in pregnancies complicated by diabetes and summarize the reported neonatal and maternal outcomes in exposed and unexposed groups. Data sources: A systematic search was performed in November 2023 using Ovid Medline and Embase databases to identify relevant studies. Study Eligibility Criteria: Articles that reported on the maternal or neonatal outcomes in pregnancies complicated by pre-gestational or gestational diabetes after exposure to antenatal corticosteroids were included in this review. Articles were excluded if they did not separately report on the outcomes experienced by women with diabetes. Methods: Maternal and neonatal outcomes of interest included neonatal respiratory distress syndrome, neonatal hypoglycemia, and maternal hyperglycemia. Key words in this search included combinations of the terms related to pre-gestational and gestational diabetes, antenatal corticosteroids, respiratory distress syndrome, hypoglycemia, and hyperglycemia. Title and abstract screening was conducted in duplicate. Results: There were 19 studies that met the inclusion criteria. There were 13 studies that presented results pertaining to neonatal respiratory distress syndrome, 14 studies discussed neonatal hypoglycemia and 5 studies discussed maternal hyperglycemia. Only 2 included studies were randomized controlled trials with the remaining 17 studies being observational. There was heterogeneity in clinical settings, study populations, type of corticosteroid administered and timing of administration across the included studies. This review found that there is no clear evidence of beneficial effect of corticosteroid administration on neonatal respiratory outcomes in pregnancies complicated by diabetes. Additionally, there was discrepancy between studies reporting on neonatal hypoglycemia with 6 studies reporting an increased incidence in this outcome after antenatal corticosteroid exposure whilst 4 studies found no difference between exposed and unexposed groups. This review identified a specific gap in the reporting of maternal hyperglycemia following antenatal corticosteroids. The limited number of studies that did report this outcome unanimously reported an increased incidence of maternal hyperglycemia after corticosteroid exposure. The majority of studies had small sample sizes of pregnancies both complicated by diabetes and exposed to corticosteroids and therefore lacked sufficient power to make robust conclusions about the influence of antenatal corticosteroids in this group. Conclusion: This review concludes that there are insufficient data regarding the risks and benefits of antenatal corticosteroid administration in pregnancies complicated by diabetes.